Review of the current state of world capture fisheries insurance - Anrooy, Raymon van (Rome : Food and Agriculture Organization of the United Nations, 2009)
This publication provides an overview of the current status of capture fisheries insurance in the world. It presents the findings of a number of regional and national review desk studies carried out between December 2006 and January 2008 covering China, Japan and India in Asia, Europe, Africa, the United States of America in North America, South America, Oceania and the Russian Federation. A summary synthesis of the studies is included along with information about the insurance market, demand and supply issues, perils covered, vessels insured, risk management methods applied and underwriting experiences. Providing guidance for the formulation of legal, policy and institutional frameworks in developing countries, it addresses decision-makers at national government levels, as well as international agencies and fisheries sector stakeholders.--Publisher's description
Keywords: Fisheries; Fisheries; Sustainable fisheries